The influence of entrepreneurial leadership style on the performance of instructors of courses and training institutions - Santosa, Tri Budi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
A This study aims to explore the impact of entrepreneurial leadership style on the performance of instructors at the Course and Training Institute in Surakarta. Employing a quantitative method, the study focuses on the entire group of LKP instructors in Surakarta, with 43 instructors selected as representatives through purposive sampling. The research instrument validation utilized the product moment correlation, while reliability was assessed using Cronbach's Alpha. Data were analyzed using multiple linear regression. The findings of this study affirm that entrepreneurial leadership style significantly contributes to the improvement of instructor performance in Surakarta, with a very low p-value of 0.000. Moreover, the percentage of entrepreneurial leadership style contribution to instructor performance reaches 40.3%